THE RISK LEVEL OF PRODUCTION AND PRICE OF RED CHILI FARMING IN KEDIRI REGENCY, EAST JAVA PROVINCE, INDONESIA - Nining Hariyani (Agricultural Socio-Economics Journal, 2017)
The purposes of this research are to analyze production and price risk level of red chili farming especially on dry land in off-season. Data are collected through interview to 47 farmers who grow red chili on dry land during the rainy season. The research results show that price risk levelis higher than production risk level.Coefficient of variation (CV) of Chili price is 0.32 and the CV of chili production is 0.05. The risk of price is higher than production risklevel due to the fact that price is more volatile and more difficult to control by farmers. Additionally, production riskis still manageable and can be controlled by farmers through the implementation of off-season cultivation technology combining by the experience of farmers in the production. However, the total production are still lower than the potential productivity due to the weather constraint. In order to reduce the level of production and price risk, farmers can make diversivication crops to secure income. In addition, farmers must actively observe price and make decision of production accordingly.